Persepsi Konsumen dan Strategi Masuk Pasar untuk Produk Tepung Bumbu Serbaguna Berbasis MOCAF yang Inovatif: Consumer Perception and Market Entry Strategy for a Novel MOCAF-Based All-Purpose Seasoning - Hastati, Dwi Yuni; Fajri, Aulia Irhamni; Febrinda, Andi Early; Anggarkasih, Made Gayatri; Trianawati, Mrr Lukie; Fatimah, Ai Imas Faidoh; Sarastani, Dewi; Mariyani, Neny; Adzkiya, M Agung Zaim; Suhaima, Nurafi Razna; Hapsari, Rianti Dyah; Nurwitri, Caecillia Chrismie; Ladystia, Syakilah Nawal; Prananingrum, Disty Isbiyanti (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2025)
This study aims to analyze consumer perceptions and preferences regarding a novel all-purpose seasoning based on Modified Cassava Flour (MOCAF) and to formulate an effective market entry strategy. A descriptive quantitative research design was employed, combining sensory evaluations and structured consumer surveys. Sensory evaluation involved 35 panelists who compared the MOCAF-based seasoning with two commercial brands, assessing attributes including taste, aroma, texture, and overall appearance. Results from the consumer survey indicated positive perceptions of the MOCAF-based seasoning, with respondents rating it favorably in terms of taste (74%), aroma (75%), and overall appeal (70%). However, price sensitivity emerged as a significant concern, with approximately 23% of respondents highlighting affordability as an issue. Demographic factors, especially education level and occupation, significantly influenced consumer perceptions. Housewives, in particular, showed greater awareness and familiarity with the product. Based on these findings, an integrated market entry strategy was developed, emphasizing market segmentation, targeting health-conscious households, particularly mothers and homemakers, and positioning the product as a healthier, gluten-free alternative to conventional seasonings. The study further recommends the implementation of educational campaigns, partnerships with influencers, and product sampling programs to enhance product awareness and build consumer trust. This research contributes to the existing body of literature on functional foods, particularly regarding sustainable local food innovations in emerging markets. The results provide practical insights for producers aiming to introduce MOCAF-based products to broader markets.